MOTIVASI ORANG TUA MENYEKOLAHKAN ANAK KE SEKOLAH ISLAM TERPADU (Studi Pada SDIT-Al-Madinah Kota Pekanbaru) - Ary Saputra; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This Study describes about Motivation of parents send their children to integrated Islamic School in Al-Madinah, Pekanbaru. Motivation Parents can be seen through some of the indicators , namely social status, facilities and infrastructure, religious values and achievements.The study population is parents who send their children in integrated school Islam Al-Madinah city of Pekanbaru. Sampling method used in this study is proportionate stratified sampling techniques and data analysis used is descriptive and quantitative analysis.Data collected by using questionnaires, interviews, and documentation contained in the tabulation of the data. The theory used is the theory of Motivation and Rational Choice Theory.The purpose of this study is for know the motivation of parents to send children in integrated Islam school Al-Madinah Pekanbaru and know the expectations of parents after child education in primary school Islam Al-Madinah Pekanbaru.Results from this study is that Motivation Parents send their children to integrated islam school Al-Madinah because the parents has to have the mindset that developed, the parents hope children are schooled in Islamic schools in the future can have a strong religious foundation, high discipline as well as various another achievement. Then besides that parents also want their children to become one of Hafiz Quran because since the beginning of the child has been taught to memorize the Quran according to class level.Keywords: Motivation, SDIT (Integrated Islam School), Parents